Visual attentional differences in psychology students with and without disabilities: a pilot study assessing the flanker task for prescriptive visual accommodative technologies - Chan, Anders; Harkinish-Murray, Zachary I.; Colmone, Sabrina; Orens, Jessica E.; Thomas, Sharon; Albanese, Nicole; McCabe, Katherine; Freitas, Rui; Bailey, Stephanie P.; Ramdhari, Ravi L.; Verrengia, Michael T.; Siddiqui, Kainaat F.; et al. (Frontiers in Psychology, 2025)
IntroductionThe percentage of college students with disabilities has been growing and has doubled in the last two decades; thus, students with disabilities are pursuing college degrees in increasing numbers. Unfortunately, this population growth has not been matched with growth in available accommodative technologies in institutions of higher learning. Colleges and universities often do not have resources to fund and provide specific accommodative technology and support for this steadily increasing population. What is worse is that there is also a lag in emergent assessment and screening tools which are required to match student disabilities with appropriate accommodative technologies, resulting in a mismatch between student needs with appropriate accommodative technologies. The present pilot study was conducted with students with a range of disabilities, such as learning disabilities, emotional or psychiatric conditions, orthopedic or mobility impairments, attention-deficit disorder/attention-deficit hyperactivity disorder, health impairments (HI), and multiple disabilities, which were assessed using a Flanker Task, specifically to determine how sensitive it was in detecting differences in their visual attention performance. This information could be used to predict whether the student would benefit from specific accommodative technologies.Materials and methodsUndergraduate psychology students with and without disabilities volunteered to participate in a triple-blind study that sought to investigate whether their visual attention performance on a 10-min Flanker Task could be used to predict which students might benefit from visual accommodative technologies. The first experiment was used as a negative control to assess whether environmental distractions could interfere with participant visual attention. The second experiment compared the Flanker Task performance of students with and without disabilities in a controlled Neuropsychology Laboratory sound-attenuated environment. The third experiment evaluated the cumulative records for percent (%) accuracy and reaction times (RTs) for students with and without disabilities to examine patterns in visual attentional performance. The fourth experiment disaggregated the students with disabilities and examined their patterns in visual attentional performance.ResultsThe results showed the Flanker Task was sensitive in detecting differences in students’ visual attention performance between noisy and controlled environments differentiated students with and without disabilities. Furthermore, when students with disabilities were aggregated, their Flanker Task cumulative records were sensitive in detecting shifts in their visual attention behavior patterns. Lastly, the Flanker Task cumulative records were also sensitive in detecting disaggregated students with disability differences in their visual attention performance.ConclusionThe pilot study proved promising that a 10-min Flanker Task can be used as an effective screening tool to match students with disabilities with appropriate accommodative technologies based on their visual attentional abilities. This type of screening tool is easy to create, has minimal cost, and can be implemented quickly. This provides colleges and universities with an easy approach to assessing the needs of students with disabilities and tailoring appropriate assistive technologies.